A Miniaturized High-Gain Flexible Antenna for UAV Applications - Xinhuan Yang; Yanzhu Qi; Bo Yuan; Yazi Cao; Gaofeng Wang (International Journal of Antennas and Propagation)
A miniaturized high-gain flexible unmanned aerial vehicle (UAV) antenna is presented in this study. The proposed antenna basically comprised of three parts of printed patch in series, etched on dielectric substrate. And, a flexible cable is loaded on the bottom of dielectric substrate. A coplanar waveguide (CPW) with asymmetric ground feeding structure is employed to provide good impedance matching. The surface current can achieve the same phase for the straight-line patch and the flexible cable, through adjusting the dimensions of the meander line patch, which increases radiation gain while maintaining the compact size. As an important merit to be highlighted, the flexible cable can greatly reduce the volume and aerodynamic drag of the antenna. It has a low-profile compact size of 196 × 15 × 0.8 mm3 (excluding flexible cable). The results show that the omnidirectional gain fluctuates within 4.5 ± 0.1 dBi in the desired band (902 MHz–928 MHz), which is high enough for the UAV application. Details of the antenna design and experimental results are presented and discussed.